Dynamic Reconfiguration of Distribution Networks Considering the Real-time Topology Variation - Mainali, Sabin; Mishra, Akhileshwor; Khan, Shahbuddin (Journal of Advanced College of Engineering and Management, 2024)
Electrical distribution networks undergo dynamic transformations due to continuous alteration and variation of loads. These alterations necessitate engineering studies aimed at optimizing the distribution networks. Reconfiguring networks stands as a critical analysis process essential for enhancing and managing distribution systems (DSs). When starting with a stable initial DS, the distribution feeders can be reconfigured by adjusting switch statuses to enhance operational performance. In this study, we introduce a dynamic reconfiguration approach that takes into account real-time variations in the initial topology. This methodology integrates dynamic topology analysis and network reconfiguration to address real-time distribution network optimization issues.. We identify the best configuration to reduce power losses and improve the voltage profile of the real-time distribution network in accordance with network reconfiguration. A new approach to dynamic reconfiguration in distribution systems (DS) is introduced, focusing on real-time changes in the initial topology rather than a fixed network structure. This method restores DS network connectivity by dynamically analyzing topology when changes in the initial configuration are identified. By aligning with the current network structure, the proposed method determines the optimal configuration for minimizing power loss and enhancing voltage profiles. As a result, this approach can be readily applied to the real-time variation in network topology during the reconfiguration of distribution systems.